Efektivitas Pemberian Rebusan Kunyit Asam Terhadap Penurunan Dismenorea - Sri Rahma Suciani; Sri - Utami; Ari Pristiana Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to determine the effectiveness of tumeric and tamarind to relieve dysmenorrhoea. The method was quasy experiment by giving tumeric and tamarind stew to the experimental group. The research was conducted on SMAN 9 Pekanbaru, toward 30 respondent which devided into two group. The first group was experimental group and the second group was control group. The sampling used purposive sampling technique, the measurement was a numeric rating scale to measure the intensity of pain. The analysis were univarite and bivariate analysis by using t-dependent sample test and mann whitney. The result showed there was a significant reduction of the intensity of pain to the experimental group after the group had taken the tumeric and tamarind stew ( p < α 0,05). Its mean that the stew was efective to relieve dysmenorrhoea. Its recomended to female student to apply the tumeric and tamarind stew as herbal medicine to relieve the dysmenorrhoea. Keywords: dysmenorrhoea, turmeric, tamarind